2015
DOI: 10.1155/2015/627837
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Three-Hour Maternal Separation Induces Depression-Like Behavior and Affects the Expression of Hippocampal Plasticity-Related Proteins in C57BL/6N Mice

Abstract: Adverse early life experiences can negatively affect behaviors later in life. Maternal separation (MS) has been extensively investigated in animal models in the adult phase of MS. The study aimed to explore the mechanism by which MS negatively affects C57BL/6N mice, especially the effects caused by MS in the early phase. Early life adversity especially can alter plasticity functions. To determine whether adverse early life experiences induce changes in plasticity in the brain hippocampus, we established an MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 33 publications
3
39
1
Order By: Relevance
“…5). Previous studies have demonstrated that early life stress may elicit depressive-like behavior [5], which was observed in the activity levels of Control pups raised by High-Active dams (Fig. 5C).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…5). Previous studies have demonstrated that early life stress may elicit depressive-like behavior [5], which was observed in the activity levels of Control pups raised by High-Active dams (Fig. 5C).…”
Section: Discussionmentioning
confidence: 56%
“…Multiple studies have demonstrated significant associations between adversive postnatal environments and the manifestation of clinical disorders later in life [24]. Modeling the effects of early life stressors in animals has largely corroborated such results; exposure to maternal separation or neglect heightens stress reactivity, aggression, and other features of clinical disorders such as depression and schizophrenia [58]. Accumulating evidence not only suggests that early life environment affects relevant genes via epigenetic modifications which may serve as biomarkers for susceptible populations [9, 10], but furthermore that environmentally-induced behavioral deficits may be transmitted to subsequent generations [1113].…”
Section: Introductionmentioning
confidence: 99%
“…This result is in agreement with previous reports (Amini‐Khoei et al, 2017; Gracia‐Rubio et al, 2015). Similarly, many studies have observed depression‐like behaviours in MS offspring in models such as the forced swim test, tail suspension test, or splash test (Amini‐Khoei et al, 2017; Bian et al, 2015; Dimatelis et al, 2012b; Hennessy et al, 2016). Anxiety‐like symptoms were evaluated by the elevated plus maze test and social preference tests, and the results indicated that MS also increases anxiety levels in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that long periods of MS result in elevated or reduced locomotor activity in the open field test (Bian et al, 2015; Wang et al, 2015). However, in our study, there were no significant differences between each group in basal locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few numbers of studies have directly examined the effect on adolescents, and the findings were varied and inconsistent. In adolescent C57BL/6 mice, some studies indicated that MS enhanced anxiety‐related and depression‐like behaviors (Bian et al, ), but others found it only increased anxiety‐related behaviors (Shin, Baek, Han, & Min, ; Shin, Han, Woo, Jang, & Min, ). In adolescent rats, MS has been shown to increase depressive behaviors during adolescence (Leussis, Freund, Brenhouse, Thompson, & Andersen, ; Lukkes, Meda, Thompson, Freund, & Andersen, ).…”
Section: Introductionmentioning
confidence: 99%